Building Tanggomo's Local Insights As A Construction Of Local Identity Through Historical Learning In Middle Schools Of Gorontalo - Mahmud, Djulia Indriani A.H; Warto, Warto; Sariyatun, Sariyatun (Universitas Sebelas Maret, 2020)
This article examines the relevance of historical learning by transforming the local value of the tanggomo to the awakening of local identity in Gorontalo. In its development., tanggomo is not only known as folklore or oral literature, but is also one of the objects of struggle for a locality and the beginning of the growth of nationalism. In its implementation, history learning must pay great attention to the growth of national identity and identity, both in the Indonesian and local realms, so that local history studies need to be used, in addition to improving the quality of history learning, as well as an effort to introduce regional wisdom. The writing in this article uses the literature study method by involving empirical and relevant literature sources.